Exposures of Lateral and Inferior Cardiac Surface for Coronary Anastomosis During Minimally Invasive Coronary Artery Bypass Grafting. Issue 1 (January 2015) - Pande, Shantanu; Gupta, Devendra; CR, Siddartha; Bansal, Anubhav; Agarwal, Surendra K.
<x xml:space="preserve">Abstract</x> Abstract Exposure of the lateral and inferior surface of the heart during off-pump coronary artery bypass grafting is associated with some degree of cardiac instability during recovery with completion of grafting. Exposure of lateral and posterior surfaces by currently available equipment is difficult in minimally invasive coronary artery bypass grafting (MICABG) owing to limited exposure. We describe an effective variation of often-used technique of pericardial stitch in exposure of cardiac surfaces during MICABG. This technique was used in 24 patients undergoing multivessel MICABG. Deep pericardial sutures were used to manipulate the exposure of cardiac surfaces. Left anterior descending artery was grafted in all 24 cases. Obtuse marginal artery was grafted in 20 cases and posterior descending artery in 12 cases. Average grafts were 2.3 per patient. There was no conversion to median sternotomy. Use of deep pericardial suture is simple technique for exposure of lateral and inferior surface during multivessel MICABG. This offers adequate exposure and operating space for easy maneuverability.